Low Risk of Irritable Bowel Syndrome after Clostridium difficile Infection. (2007) - Piche, Thierry; Vanbiervliet, Geoffroy; Pipau, Fernand Girard; Dainese, Raffaella; Hébuterne, Xavier; Rampal, Patrick; Collins, Stephen M
Abstract : OBJECTIVE: The incidence of postinfectious irritable bowel syndrome (IBS) ranges between 4% and 32% of individuals after bacterial or parasitic infection. This study analyzed IBS symptoms in hospitalized patients three months after a symptomatic Clostridium difficile infection. PATIENTS AND METHODS: All patients with a proven, symptomatic C difficile infection identified in the department of bacteriology over a four-month period were considered for enrolment. Patients were excluded in cases of pre-existing IBS or other organic gastrointestinal diseases. Patients completed both modified Talley and Rome II questionnaires within five days of clinical improvement with metronidazole and at three months postinfection, when stools were cultured and C difficile toxins were examined to exclude ongoing infection. RESULTS: Twenty-three patients were evaluated three months after infection with C difficile . Just after infection, 15 patients were symptom free, whereas eight patients exhibited symptoms suggestive of IBS. Three months after infection, 22 patients remained symptom free, whereas one patient presented with symptoms indicative of IBS. That female patient had a prolonged infection without vomiting. CONCLUSIONS: We have shown that while transient functional bowel disorder occurred in 34.7% of patients (eight of 23 patients) recently infected with C difficile, only 4.3% of patients (one of 23 patients) had symptoms indicative of IBS after three months (ie, postinfectious IBS). Because an age-related reduction in immune responsiveness has been documented, it can be speculated that the low incidence of postinfectious IBS may be explained by the older age of the study population. Therefore, it cannot be excluded that the findings may be different in younger patients.